Modeling the risk of an organizational development portfolio - Micán, Camilo (2023)
Project portfolios have been seen as a structured way to implement business changes based on the organizational strategic goals. In this regard, portfolio risk could be related with the risk factors impact on strategic objectives. However, risk factors related to the project portfolio do not directly impact strategic objectives; their strategic impact is related to how the portfolio delivers value to the organization. This paper describes a risk assessment implementation conducted in an organizational development project portfolio case study, showing how the project portfolio risk is linked with the strategic goals. This was accomplished based on a proposed conceptualization for project portfolio risk assessment (PPRA). The risk assessment was conducted considering interdependencies between risk factors and how risk factors derived from both project and portfolio levels impact primarily on projects within the portfolio. And then, considering how the risk factors prior impact is transferred from projects to portfolio outcomes and, in turn, to strategic objectives. The risk assessment results allowed to identify the most influential risk factors for the portfolio case study, representing an essential input for designing the risk response plan.